Friedrich Schleiermacher’s Pathways of Translation - de Bończa Bukowski, Piotr (De Gruyter, 2023)
This interdisciplinary study introduces readers to Friedrich Schleiermacher’s diverse pathways of reflection and creative practice that are related to the field of translation. By drawing attention to Schleiermacher’s various writings on a range of subjects (including philology, criticism, hermeneutics, dialectics, rhetoric and religion), the author makes it clear that the frequently cited lecture Über die verschiedenen Methoden des Übersetzens (On the Different Methods of Translating) represents but a fraction of Schleiermacher’s contributions to modern-day insights into translation. The analysis of Schleiermacher’s various pathways of reflection on translation presented in this book leads to the conclusion that translation is part of the essence of the world, as it is a fundamental tool of our cognition and a foundation of our existence. In Schleiermacher’s works, transfer, translation, mediation, and communication underpin our very existence in the world and our self-awareness. At the same time, they represent fundamental categories for a project that focuses on the consolidation and assimilation – through translation – of that which is foreign, different, diverse
10.1515/9783110745474
Keywords: Interdisziplinäre Studien; Schleiermacher; Übersetzung; RELIGION / Christian Theology / History